2014
DOI: 10.1590/s1415-43662014000400012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the water quality in a large reservoir in semiarid region of Brazil

Abstract: A B S T R A C TThe aim of this study was to identify spatial and temporal variations in water quality of Orós reservoir, Ceará, Brazil, as well as the sources of contamination. To get this information the Principal Component Analysis (PCA) and Cluster Analysis (CA) was used. Water samples were collected at seven (geo-referenced) points, from April 2008 to March 2011, totalling 4,032 samples. The following attributes of the waters were analysed: temperature, pH, CE, Ca , turbidity, colour, Sechi transparency, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 17 publications
1
23
0
5
Order By: Relevance
“…Segundo Richards (1954), valores abaixo de 0,25 dS m -1 são considerados excelentes para irrigação em relação ao problema de salinização do solo. Lopes et al (2014), em seu estudo no reservatório de Orós no Nordeste do Brasil, concluíram que as águas deste reservatório, quando utilizadas na agricultura irrigada, não apresentam risco de acumulação de sódio e condutividade elétrica preocupante, uma vez que encontraram valores de 1,04 mmol c L -1 e 0,19 dS m -1 para sódio e condutividade elétrica, respectivamente. De acordo com o diagrama de Richards (1954), que classifica as águas para fins de irrigação, utilizando os dados de RAS e Condutividade Elétrica, a água estudada neste trabalho foi classificada como C1S1 (baixo risco de salinização e baixa concentração de sódio).…”
Section: Resultsunclassified
“…Segundo Richards (1954), valores abaixo de 0,25 dS m -1 são considerados excelentes para irrigação em relação ao problema de salinização do solo. Lopes et al (2014), em seu estudo no reservatório de Orós no Nordeste do Brasil, concluíram que as águas deste reservatório, quando utilizadas na agricultura irrigada, não apresentam risco de acumulação de sódio e condutividade elétrica preocupante, uma vez que encontraram valores de 1,04 mmol c L -1 e 0,19 dS m -1 para sódio e condutividade elétrica, respectivamente. De acordo com o diagrama de Richards (1954), que classifica as águas para fins de irrigação, utilizando os dados de RAS e Condutividade Elétrica, a água estudada neste trabalho foi classificada como C1S1 (baixo risco de salinização e baixa concentração de sódio).…”
Section: Resultsunclassified
“…The effectiveness of this method has been proven by many other studies with similar topics. As such, Lopes et al (2014) used multivariate statistical methods to assess the quality of water behind a large reservoir in Brazil [28]. They concluded that these techniques are very effective in reducing the number and frequency of samplings and this can lead to considerable savings in the cost of tests.…”
Section: Statistical Test Results By Monthmentioning
confidence: 99%
“…Um total de 10 campanhas foram realizadas de abril de 2008 até fevereiro de 2010 durante dois períodos: estação chuvosa aquela com precipitação pluviométrica mensal maior que 50 mm (dezembro a maio) e o período seco (junho a novembro), assim como empregado por Ferreira et al (2015).…”
Section: Methodsunclassified